Has There Been a Change Between Combat Time in Male Judo? Analysis of the Top 20 Athletes by Weight Division Between the 2016-20 Olympic Cycles - Aedo-Munoz, E (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
This study compared male judo combat time in international competitions between the 2016 and 2020 Olympic cycles, by weight divisions. We analysed 1380 videos of male judo combat from top 20 in the World ranking by weight division. The 2020 cycle had a lower combat time and a higher occurrence of Golden Score (GS) compared to the 2016 cycle (combat time: 2020= 206.9, 2016= 240.3 seconds; GS time: 2020= 95.1, 2016= 77.6 seconds; p<0.001; GS occurrence: 2020= 27%, 2016= 6%; p<0.05). The 66kg and 73kg spent the most time and the +100kg category spent the least time in the GS than the other divisions, in both Olympic cycles. However, in the 2020 cycle compared to 2016, the 66kg was the only that reduced the combat time on the GS (p= 0.002), the 81kg and +100kg had a change in the distribution of combat closure minute-by-minute [81kg(2016)= 28%, 81kg(2020)= 68% finished until the 4th minute of Regular Time; +100kg(2016)= 25%, +100kg(2020)= 50% finished until the 3rd minute of Regular Time; p= 0.003 for both]. These data must be considered when prescribing male judo training for specific performance.